Cartas de amor à Divina: uma leitura imagético-verbal sobre a produção oficiosa de Di Cavalcanti - Almeida, Sullivan Bernardo de (2012)
Di Cavalcanti's official production is the subject of studies in many disciplines, each of which takes its own particular approach. This official production is understood to be all of the verbal-imagery work produced by the artist throughout his career in order to meet the demands of the art market. However, the book Cartas de Amor à Divina, a compendium containing letters, cards, drawings and reproductions of portraits of Ivette Bahia Rocha, the "Divina", is understood as unofficial production. Published in 1987, the book records the fifteen-year loving relationship of Di Cavalcanti and Ivette. The set reveals the drama of an older man, 62 at the time, who cannot control a 23-year-old woman. Ivette met the painter in 1959 on a visit to his studio in Copacabana, Rio de Janeiro, and became an assiduous studio guest, occupying, little by little, all spaces of the artist's life: she was his secretary, financial administrator, muse and wife. The relationship ended in 1974, during the middle of a political and cultural transformation in Brazil. Structured from the concepts that guide the study of History of Culture, this study is dedicated to analyzing the verbal imagery content contained in Di Cavalcanti's epistolary, which was transformed into a book in 1987. The goal is to identify the reasons for which the relationship's dynamic was conflicted and how such subversions interfered or not in the painter s artistic production.